2010
DOI: 10.1007/s11104-010-0560-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant species richness and evenness on soil microbial community diversity and function

Abstract: Understanding the links between plant diversity and soil communities is critical to disentangling the mechanisms by which plant communities modulate ecosystem function. Experimental plant communities varying in species richness, evenness, and density were established using a response surface design and soil community properties including bacterial and archaeal abundance, richness, and evenness were measured. The potential to perform a representative soil ecosystem function, oxidation of ammonium to nitrite, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
103
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(113 citation statements)
references
References 71 publications
6
103
1
3
Order By: Relevance
“…Therefore, these differences in the litter contribution influenced the soil microbial biomass across the gradient. Additionally, some studies have reported that more diverse plant communities positively affect soil microorganisms (Berg & Smalla, 2009;Wallenstein et al, 2007;Malchair et al, 2010;Lamb et al, 2011). Wallenstein et al (2007) evaluated the bacterial community between Alaskan tussock and shrub tundra vegetation and found that plant communities regulate bacterial communities through the quantity and chemical quality of plant litter in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these differences in the litter contribution influenced the soil microbial biomass across the gradient. Additionally, some studies have reported that more diverse plant communities positively affect soil microorganisms (Berg & Smalla, 2009;Wallenstein et al, 2007;Malchair et al, 2010;Lamb et al, 2011). Wallenstein et al (2007) evaluated the bacterial community between Alaskan tussock and shrub tundra vegetation and found that plant communities regulate bacterial communities through the quantity and chemical quality of plant litter in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…1). The Truelove Lowland site (75°40=N, 84°35=W) has already been extensively described (6,37,64). The average July soil temperature in the upper 5 cm in 2008 was 13°C, with a maximum value of 24°C and a minimum of 6°C (17).…”
Section: Methodsmentioning
confidence: 99%
“…The topography of Truelove Lowland is distinguished by a series of raised beach crest ridge, lower foresope, and wet sedge meadow with regosolic static cryosols, brunisolic eutric turbic cryosols, and gleysolic turbic cryosols, respectively (64). The mean annual air temperature is approximately Ϫ16°C, with the highest recorded daily temperature of 21°C in July and Ϫ45°C as the lowest monthly temperatures (6,37). The total annual precipitation is about 185 mm, with 36 mm as rain.…”
Section: Methodsmentioning
confidence: 99%
“…Many researchers have concentrated on the influences of plant community species richness and composition on belowground bacterial communities (Zak et al, 2003;Lamb et al, 2011), yet the relationships between plant and soil bacteria in richness are often inconsistent with distinct study methods or space and time lags. In general, positive effects of plant species richness on bacterial community richness could be attributed to the increasing soil nutrient pools and root exudate chemistry (Zak et al, 2003;Loranger-Merciris et al, 2006).…”
Section: Introductionmentioning
confidence: 99%